A peer support dietary change intervention for encouraging adoption and maintenance of the Mediterranean diet in a non-Mediterranean population (TEAM-MED): lessons learned and suggested improvements. (30th January 2023) - Appleton, Katherine M.; McEvoy, Claire T.; Lloydwin, Christina; Moore, Sarah; Salamanca-Gonzalez, Patricia; Cupples, Margaret E.; Hunter, Steven; Kee, Frank; McCance, David R.; Young, Ian S.; McKinley, Michelle C.; Woodside, Jayne V.
Abstract: Peer support interventions for dietary change may offer cost-effective alternatives to interventions led by health professionals. This process evaluation of a trial to encourage the adoption and maintenance of a Mediterranean diet in a Northern European population at high CVD risk (TEAM-MED) aimed to investigate the feasibility of implementing a group-based peer support intervention for dietary change, positive elements of the intervention and aspects that could be improved. Data on training and support for the peer supporters; intervention fidelity and acceptability; acceptability of data collection processes for the trial and reasons for withdrawal from the trial were considered. Data were collected from observations, questionnaires and interviews, with both peer supporters and trial participants. Peer supporters were recruited and trained to result in successful implementation of the intervention; all intended sessions were run, with the majority of elements included. Peer supporters were complimentary of the training, and positive comments from participants centred around the peer supporters, the intervention materials and the supportive nature of the group sessions. Attendance at the group sessions, however, waned over the intervention, with suggested effects on intervention engagement, enthusiasm and group cohesion. Reduced attendance was reportedly a result of meeting (in)frequency and organisational concerns, but increased social activities and group-based activities may also increase engagement, group cohesion and attendance. The peer support intervention was successfully implemented and tested, but improvements can be suggested and may enhance the successful nature of these types of interventions. Some consideration of personal preferences may also improve outcomes.